Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Une histoire de Montréal. Édition revue et augmentée - Linteau, Paul-André (Boréal compact, 2022)

A very Partisan Press - Bérubé, Harold (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Avenir (L'); La Fontaine, Louis-Hippolyte; Minerve (La); Montreal Gazette; Montreal Herald; Papineau, Louis-Joseph; Partis politiques

Le collier d'office - Guiard, Jean-Paul (Il était une fois...Montréal-Nord, 2022)
Keywords: Maires; Montréal-Nord

Trouve-Toi Une Job ! : Petite Histoire Des Luttes Pour Le Droit À L'assurance-Chômage - Mouvement Action-Chômage Montréal (Écosociété, 2022)
Keywords: Chômage; Groupes populaire

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Hôtellerie; Marchés

Discovering Parliament in Montréal - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

Kingston to Montréal. Inside the Parliamentary Libraries - Gallichan, Gilles (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Moving the Seat of Parliament. From Kingston to Montréal - Gallichan, Gilles (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Parlement

Construire une citoyenneté urbaine par le droit de vote au municipal: lois électorales et contestations militantes à Montréal de 1965 à 1974 - Robert, Vincent (Université de Montréal, 2022)
Keywords: Femmes; Libéralisme; Montreal Local Council of Women; Rassemblement des citoyens et citoyennes de Montréal; Élections

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

Le Montréal juif – (3e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise; Cecchini, Lisa; Hamilton, Patricia; Knowles, Terry (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

« Nous ne parlerons pas de la guerre » : la participation oubliée de l’Université de Montréal à la Seconde Guerre mondiale - Walling, Jeremy John (Cahiers d'histoire, 2022)
Keywords: Guerre; Quartier latin (Le); Université de Montréal; Étudiants

Les élections au temps des patriotes : conflits, violence et politisation en contexte électoral (1820-1834) - Théberge, Samuel (Université du Québec à Montréal, 2022)
Keywords: Minerve (La); Montreal Gazette; Montreal Herald; Élections

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

St Anne's Market. A Long-Awaited Project - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Sainte-Anne (marché)

A Building Transformed. From Market to Parliament - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Marchés; Parlement; Sainte-Anne (marché)

Two Commemorative Pitchers, or the End of an Era. 1846. Repeal of the Corn Laws - Pothier, Louise (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

In Response to the Unrest, Petitions in Support of the Queen Poured in. Denouncing the Tories to Save the Empire - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Mouvement annexionniste; Parlement; Réformistes; Torys; Émeutes

After the Fire Comes the Investigation. Citizens Give Testimony - Roy, Alain; Horner, Dan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Torys; Émeutes

Rebellion Losses Bill: Mere Pretext or the Real Cause of the Burning of Parliament - Leblanc, Jean-François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Rébellions; Réformistes; Torys; Émeutes

1849. To the Parliament House! - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Incendies; Parlement; Torys; Émeutes

Travailleuses anonymes et modernité énergétique. L’industrie électrique et gazière et l’économie domestique à Montréal, 1904-1959 - Hatton-Proulx, Clarence (Revue d'histoire de l'Amérique française, 2022)
Keywords: Femmes; Montreal Light, Heat and Power; Travail; École ménagère; Électricité

Le Montreal Local Council of Women et la Fédération nationale Saint-Jean-Baptiste: Entre identités et marginalisations, 1893-1914. - Béliveau, Geneviève (Consommation et identité: production et occupation de l’espace aux XIXe et XXe siècles. Actes des 25e et 26e colloques étudiants du CIEQ, 2022)
Keywords: Bourgeoisie; Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Local Council of Women

Histoire du Conseil régional FTQ Montréal métropolitain. Les années 1986-2021: Entre persévérance et renouvellement - Bédard, Caroline; Busic, Milan (Service aux collectivités de l'Université du Québec à Montréal, Conseil régional FTQ Montréal, 2022)
Keywords: Fédération des travailleurs et des travailleuses du Québec (FTQ); Grèves; Travail

Oser sa voix. La galerie Roger Bellemare (1971-2021) - Lacroix, Laurier (Presses de l'Université de Montréal, 2022)
Keywords: Expositions

Scott, Brandtner, Eveleigh, Webber: revoir l'abstraction montréalaise des années 1940 - Trépanier, Esther (Presses de l'Université de Montréal, 2022)
Keywords: Peinture

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Femmes et cinéma d'animation: un corpus féministe à l'Office national du film du Canada (1939-1989) - Saint-Pierre, Marie-Josée (PUM, 2022)
Keywords: Cinéma; Femmes; Féminisme; Office national du film

Dictionnaire historique des gens du livre au Québec - Aubin, Paul; Luneau, Marie-Pier; Vincent, Josée (Les Presses de l'Université de Montréal, 2022)
Keywords: Imprimerie

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Archambault au service des Québécois depuis 1896 - Bergeron, Normand (Il était une fois...Montréal-Nord, 2022)
Keywords: Commerce de détail; Librairie; Magasins; Musique

Léon Bellefleur - Guiard, Jean-Paul (Il était une fois...Montréal-Nord, 2022)
Keywords: Peinture

Les Pharmacies Leduc, 100 ans d'existence - Leduc, Guy (Il était une fois...Montréal-Nord, 2022)
Keywords: Pharmacie

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Soundways Montreal to La Cloche - Laxer, Daniel Robert (Listening to the Fur Trade. Soundways and Music in the British North American Fur Trade, 1760-1840, 2022)
Keywords: Autochtones; Fourrure; Marchands

''L’autisme, cet inconnu'' : représentations expertes et populaires du trouble du spectre de l’autisme dans les quotidiens montréalais de 1970 à 1998 - El-Sabbagh, Marianne (Université de Montréal, 2022)
Keywords: Devoir (Le); Presse (La)

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Histoire de la biomédecine au Québec : la physiologie cardio-respiratoire à l'Institut Lavoisier de Montréal (1950-1956) - Ouimet, Benoit (Université du Québec à Montréal, 2022)

'' Une lamentable tragédie '' : la représentation des homicides québécois dans la presse francophone et anglophone au Québec entre 1885 et 1915 - Pilote, Gina (Université Laval, 2022)
Keywords: Criminalité; Montreal Gazette; Presse (La)

Former et être formée au travail domestique : l'enseignement ménager et la couture à l'école publique québécoise (1937-1969) - Brisebois, Marilyne (Université Laval, 2022)
Keywords: Commission des écoles catholiques de Montréal; Femmes; Étudiants

Le Québec anglophone: une communauté distincte du reste du Canada? : étude comparative des positions éditoriales de deux journaux anglophones - The Gazette et The Globe and Mail - en rapport avec certains débats publics au Québec et au Canada de 1976 à 1982 - Lacasse, Chantal (Université Laval, 2022)
Keywords: Anglophones; Francophones; Fédéralisme; Indépendantisme; Montreal Gazette; Nationalisme

Les premières institutions bancaires de la rue Masson - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Banque Canadienne nationale; Banque d'Hochelaga; Banque de Montréal; Banques

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Le Comité d’Habitation de Montréal - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Groupes populaires; Logement

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

Le parc olympique de Montréal à la croisée d'ambitions impérieuses - Vanlaethem, France (ARQ - Architecture & Design Québec, 2022)
Keywords: Jeux olympiques; Parcs; Stade olympique

‘We have always been here’: Busking, urban space and economy of Montreal - Chatterjee, Piyusha (Université Concordia, 2022)

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Sir Hormisdas Laporte: Homme d'affaires et maire de Montréal (1850-1934) - Saint-Pierre, Marjolaine (Septentrion, 2022)
Keywords: Maires; Philanthropie

Le travail du métal à Montréal au XVIIe siècle. Des métiers '' d’avenir '' ? - Blouin, Sonia (2022)
Keywords: Armuriers; Fer et acier

“A Curse or a Blessing?”: Montreal Jews and the Politics of 1960s Quebec - Lacasse, Simon-Pierre (Canadian Historical Review, 2022)
Keywords: Juifs; Nationalisme

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Recherche ou lobbyisme ? L’Institut économique de Montréal et le réchauffement climatique depuis 1999 - Lamy, Guillaume (Politique et Sociétés, 2022)
Keywords: Climat; Libéralisme

Les ateliers d’histoire, issus de l’action citoyenne au coeur des quartiers montréalais - Carbonneau, Réjean (Cap-aux-Diamants, 2022)
Keywords: Atelier d'histoire d'Hochelaga-Maisonneuve; Histoire

Le travail traditionnel dans les carrières de calcaire de Montréal: un prélude à la carrière Rhéaume - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Artisans; Carrière; Charretiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

Histoire et pratique d’érudition au XIXe siècle. Le cas de la Numismatic and Antiquarian Society of Montreal - Vaudry-L., Flavie (Cap-aux-Diamants, 2022)
Keywords: Numismatie

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Logement

Looking Around: The Architecture of Medical Education - Adams, Annmarie (Transforming Medical Education: Historical Case Studies of Teaching, Learning, and Belonging in Medicine, 2022)
Keywords: Médecine; Université McGill

Expo 67 and Its World: Staging the Nation in the Crucible of Globalization - Moyes, Craig; Palmer, Steven (McGill-Queen's University Press, 2022)
Keywords: Expositions

Red mitten nationalism: sport, commercialism, and settler colonialism in Canada - Fresco, Estée (McGill-Queen's University Press, 2022)
Keywords: Autochtones; Jeux olympiques; Nationalisme

Faire mouvement: les quarante ans du Mouvement d'éducation populaire et d'action communautaire du Québec - Collectif Faire Mouvement (Rue Dorion, 2022)
Keywords: Groupes populaire

« Il y a plus de crime à détruire un enfant, qu'à le faire » : traitement communautaire et judiciaire de l'infanticide en Nouvelle-France (1671-1747) - Chasle, Ariane (Université de Montréal, 2022)
Keywords: Criminalité; Enfants; Tribunaux

It Was a Man's World: Blaine Baker and the Writing of Canadian Legal History, 1981-2018 - Young, Brian (Law, Life, and the Teaching of Legal History. Essays in Honour of G. Blaine Bake, 2022)
Keywords: Ensiegnants; Histoire; Historiens; Université McGill

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels